Conflicting Loyalties: Cognitive Abstraction Drives Whistleblowing Behavior Among Those Who Value Loyalty. - van Houwelingen, Gijs; Bobocel, D. Ramona; Okimoto, Tyler (Social Justice Research, 2025)
Potential whistleblowers, that is, people contemplating revealing potentially damaging information about unethical or unlawful behavior to a third party, are often described as facing a conflict between loyalty and fairness. Yet, whistleblowers often may feel a sense of conflicting loyalties: loyalty towards the party (e.g., a colleague) that may be damaged by their blowing the whistle and loyalty towards the party (e.g., society at large) that may benefit. Understanding how people deal with such conflict of loyalties is critical for increasing whistleblowing and reducing unethical behavior. In three studies (total N = 929), we draw on construal level theory to demonstrate that, when loyalty motives are salient, the level of abstractness at which people construe a whistleblower dilemma affects whistleblowing behavior. Because the party that stands to benefit from whistleblowing is typically more global than the party that will be damaged, cognitive abstraction increases whistleblowing behavior relative to concreteness, particularly when loyalty (vs. fairness) is a salient motive. Moreover, Study 3 findings reveal that cognitive abstraction predicts whistleblowing through increased identification with global entities among people for whom loyalty is more salient. Hence, we demonstrate that whistleblowing decisions are influenced not only by the salience of certain moral motives, but also the way that people construe whistleblower dilemmas, namely, relatively abstractly or concretely. Altogether, our research offers a novel understanding of whistleblowing behavior—as a conflict between loyalties—and identifies a cognitive mechanism for promoting whistleblowing and reducing unethical behavior.